Impact of a 12-month Inflammation Management Intervention on the Dietary Inflammatory Index, inflammation, and lipids. (April 2019) - Turner-McGrievy, Gabrielle M.; Wirth, Michael D.; Shivappa, Nitin; Dunn, Caroline G.; Crimarco, Anthony; Hurley, Thomas G.; West, Delia S.; Hussey, James R.; Hébert, James R.
Summary: Background and aims: The objective of this study was to assess the feasibility (ability to recruit participants and develop the 12-month intervention), acceptability (retention of participants in the intervention), and impact on systemic inflammation and Dietary Inflammatory Index (DII®) scores over a 12-month DII-based intervention. Methods: Adults were recruited to participate in a self-selection trial (intervention: n = 61, in-person classes; control: n = 34, newsletters). Classes included participatory cooking and dietary recommendations focused on consuming a plant-based diet rich in anti-inflammatory foods (spices, vegetables, etc.). Changes in markers of inflammation, lipids, and DII were analyzed using general linear models with repeated measurements. Results: At 3 months, intervention participants had significantly lower DII scores (−2.66 ± 2.44) compared to controls (−0.38 ± 2.56) (p < 0.01); but not at 12 months ( P = 0.10). The only biomarker to approach a significant group effect or group-by-time interaction was CRP ( P = 0.11 for the group-by-time interaction). CRP decreased by −0.65 mg/L (95%CI = 0.10–1.20, P = 0.02) at 12 months in the intervention group; no significant decrease was seen for the control group. With both groups combined at 3 months, those with the greatest decrease/improvement in DII score (tertile 1) compared with those whose scores increased (tertile 3) had greater reductions in CRP (−1.09 vs. +0.52 mg/L, P = 0.04), total cholesterol (−9.38 vs. +12.02 mg/dL, P = 0.01), and LDL cholesterol (−11.99 vs. +7.16 mg/dL, P = 0.01). Conclusions: Although the intervention group had reductions in DII and CRP, main inflammation and lipid outcomes did not differ between groups. Overall, those participants with the largest reduction in DII scores had the largest reductions in CRP and LDL and total cholesterol. Future interventions may need to have more components in place to support maintenance and continued reductions in the DII. Clinicaltrials.gov identifier: NCT02382458. Highlights: At 3 months, intervention participants had significantly lower DII scores vs. controls. Those who improved DII the most had the greatest improvements in CRP and lipids. Results indicate that more support is needed for sustaining long-term dietary change.